Pengaruh Investment Opportunity Set, Konservatisme Akuntansi Dan Pertumbuhan Laba Terhadap Kualitas Laba Pada Perusahaan Manufaktur Di Indonesia - Widyastuti, Niken; Sunarto, Sunarto (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to provide empirical evidence on the influence of Investment Opportunity Set, Conservatism, and Profit Growth on Earnings Quality in manufacturing companies listed on the Indonesia Stock Exchange (BEI). Profit growth reflects the company's ability to increase earnings over time, while earnings quality reflects the extent to which reported earnings reflect the actual performance of the company. This study uses financial data from manufacturing companies during the period 2018-2022 with 146 observations as the sample. The data used are secondary in nature. Data analysis is performed using multiple regression analysis with the assistance of SPSS 21 software. The research findings indicate that the Investment Opportunity Set and Accounting Conservatism have a positive effect on earnings quality, while Profit Growth has a negative impact on earnings quality. Keywords: Earnings Quality, Investment Opportunity Set, Conservatism, Profit Growth